Early and midterm results of extended septal myectomy: Indian experience. Issue 12 (16th September 2021) - Kumar, Narendra; Kanna, Sharmil; Goel, Himanshu; Mohanty, Arun; Mohan, Rajat; Dubey, Sumir; Shad, Sujay
Abstract: Background and Objectives: Hypertrophic obstructive cardiomyopathy (HOCM) is a genetic disorder, which is a cause of significant morbidity and sudden cardiac death. Extended septal myectomy (ESM) is the therapeutic gold standard to treat left ventricular outflow tract obstruction (LVOTO) in HOCM resulting in long‐term symptomatic relief. The aim of the study was to assess the impact of ESM on midterm symptom relief, LVOTO, and survival in patients suffering from HOCM in the Indian population. Methods: We retrospectively analyzed clinical data of 36 consecutive symptomatic patients with HOCM having symptoms refractory to medical treatment and LVOTO with resting gradient ≥ 50 mmHg and who underwent ESM at our institution from 2010 to 2019. Preoperative and postoperative transthoracic echocardiography was performed to assess left ventricular outflow tract (LVOT) gradient, septal thickness, and assessment of valvar and cardiac function. Results: ESM was performed successfully in all 36 patients. The mean preoperative LVOT gradient was 113.06 ± 36.70 mmHg and decreased to 15.17 ± 7.30 mmHg ( p < .0001) in the initial postoperative period. There were two in‐hospital deaths (5.6%). There was no further mortality in the subsequent follow‐up. The mean septal thickness was 23.89 ± 5.77 mm preoperatively and 13.17 ± 3.48 mm ( p < .0001) postoperatively. During a mean follow‐up of 2 years, the NYHA functional class improved from 3.50 ± 0.70 (III–IV) to 1.50 ± 0.70 (I) ( p < .0001). Conclusions: ESM results in immediate abolition of mechanical obstruction to LVOT with normalization of left ventricular pressure and eliminates symptoms associated with HOCM.